Learning Style Preferences of Dental Students, Karachi (Medical Forum Monthly, 2024)
Objective: The prime objective of the study is to determine the learning style preference of dental students in Jinnah Medical and Dental College, Karachi.Study Design: Cross-sectional Descriptive StudyPlace and Duration of Study: The study was conducted in Jinnah Medical and Dental College on students of Dentistry, first year through final year. VARK™ questionnaire version 7.8© was distributed and data was collected between 01 November to 30 November, 2014.Materials and Methods: Total 200 questionnaires were sent out. 160 students who consented to participate in the study were included and those who refused were excluded. Descriptive statistics was used to identify the learning style preferences of the students. The VARK scores were recorded on Excel sheet. Scoring algorithms especially designed for VARK research, available on its website were used for data management and description.Results: 51% of the students (n=82) preferred a uni-modal learning style, of which Aural was the most common. 47% of the dental students (n=75) used all four modes for learning while 2% preferred bi-modal (n=3). None of the students were tri-modal.Conclusion: In conclusion, majority of students preferred uni-modal followed by the group which preferred all modes of presentation.